The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5935/0034-7280.20160009
|View full text |Cite
|
Sign up to set email alerts
|

Falls and quality of life of people with cataracts

Abstract: RESUMOObjetivo: Investigar a associação entre quedas e qualidade de vida em idosos com catarata. Métodos: Tratou-se de estudo observacional com delineamento transversal, realizado no Distrito Federal, Brasil, com uma amostra de 38 idosos comunitários divididos em dois grupos: idosos caidores (n=18) e idosos não caidores (n=20). Avaliou-se por meio do instrumento National Eye Institute -Visual Function Questionnaire 25 (NEI-VFQ 25) a saúde geral dos indivíduos da amostra, assim como a qualidade de vida relacion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
2
9
0
3
Order By: Relevance
“…The cataract group presented the lowest final score, this finding was confirmed by other HRQOL studies [9] , presumably related to the high degree of interference of this reversible cause of visual loss on daily activities.…”
Section: Discussionsupporting
confidence: 80%
“…The cataract group presented the lowest final score, this finding was confirmed by other HRQOL studies [9] , presumably related to the high degree of interference of this reversible cause of visual loss on daily activities.…”
Section: Discussionsupporting
confidence: 80%
“…As well as presenting the factors that predispose the individual to falls, it was important to address the consequences that these events have on the lives of the elderly. A reduction in functional capacity, the fear of suffering other falls, the restriction of basic activities of daily living and, above all, the exposure to a greater risk of institutionalization, leading to an increased use of specialized services and generating high costs for public services, are important issues identified in this study and which corroborate other research on the theme 23,24 .…”
Section: Extrinsic Factors Intrinsic Factorssupporting
confidence: 87%
“…Being female, aged 60 to 69 years and living with a significant other were the majority among the elderly who suffered a fall. Studies have shown that being female is a risk factor for falls (5,10,25) . The prevalence of elderly women in the context of aging is due to the higher life expectancy, being called feminization of old age.…”
Section: Discussionmentioning
confidence: 99%